Assessment of Singapore's attractiveness as a M.I.C.E destination. - Seet, Ivy Pei Shan. (2008)
This study seeks to evaluate the attractiveness of Singapore as a M.I.C.E destination compared to the regional competitors as Singapore continues to reach bold targets amidst the future challengers in the M.I.C.E industry.